Development strategy of nusantara capital city as a global halal hub - Muh Shadiqul Fajri AF (Nur Science Institute, 2026)
This study examined the strategic potential of Nusantara Capital City (IKN) to be developed as a global Halal Hub in support of the Indonesia Emas 2045 vision. A qualitative approach was employed using secondary data derived from government policy documents, the Nusantara Smart City Blueprint, and internationally indexed academic literature. Content analysis and comparative analysis were conducted to identify key themes, supporting factors, and challenges in positioning IKN within the global halal ecosystem. The findings indicated that the success of IKN as a Halal Hub depended on the integration of physical logistics infrastructure, such as multimodal transportation, segregation facilities, and cold chain systems, with smart digital technologies, including Internet of Things sensors, blockchain, and centralized monitoring systems. This integration strengthened transparency, traceability, and halal compliance while enhancing global market trust. The study also revealed the importance of human resource readiness and regulatory harmonization to ensure competitiveness. The proposed conceptual framework contributed to integrating smart city development with halal supply chain governance.This study examined the strategic potential of Nusantara Capital City (IKN) to be developed as a global Halal Hub in support of the Indonesia Emas 2045 vision. A qualitative approach was employed using secondary data derived from government policy documents, the Nusantara Smart City Blueprint, and internationally indexed academic literature. Content analysis and comparative analysis were conducted to identify key themes, supporting factors, and challenges in positioning IKN within the global halal ecosystem. The findings indicated that the success of IKN as a Halal Hub depended on the integration of physical logistics infrastructure, such as multimodal transportation, segregation facilities, and cold chain systems, with smart digital technologies, including Internet of Things sensors, blockchain, and centralized monitoring systems. This integration strengthened transparency, traceability, and halal compliance while enhancing global market trust. The study also revealed the importance of human resource readiness and regulatory harmonization to ensure competitiveness. The proposed conceptual framework contributed to integrating smart city development with halal supply chain governance.